Enhancing Teachers’ Literacy Competence through Critical Writing in Digital Era - Moh Yamin (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
The future education challenge to respond the strategic need for human resources development is by requiring any teachers to be able to be persons who are responsive and critical towards development dynamics. Teachers’ literacy competence by enhancing critical writing competence is the necessity. This article aims to discuss the literacy positioning to strengthen teachers’ capacity. By enlarging the knowledge capital, it contributes towards teachers’ strength in elaborating any issues to write. There will be critical writing competence when the teachers own a number of knowledge resources called literacy capacity. More literate the teachers are, they will be able to be critical writers in which of being able to write much whatever it is. Digital era as the other variant has the effect towards teachers’ positioning to be the persons being involved in developing the self-competence. The digital era known as disruptive era offers new way so that the teachers can access the information quickly and easily. This research is based on critical literature review in which every relevant theories and relevant research results become the authentic resources to enrich this discussion. The data analysis is descriptive method in qualitative approach.